THE EFFECT OF INSTAGRAM INFLUENCERS CONTENT EXPOSURE ON THE MOTIVATION FOR ONLINE SELF- DISCLOSING - Zahara, Fitria Nissa; Effendi, Ridwan; Sukmayadi, Vidi (Universitas Pendidikan Indonesia, 2020)
Social media has been growing rapidly, and it revolves around self-disclosure. Social media provide the opportunity to showcase oneself, begin and extend oneâ€™s social circle, exchange content and even personal information in order to deepen online connections to others. Instagram as the most influential social media nowadays, triggers its users to perform OSD. The use of social media is indeed one of the predictors that have an impact. But apart from that, there is an exposure created by the presence of a media. The effect of media exposure also often affects a person in self-disclosure on social networks. The independent variable in this study is Instagram influencer content exposure. As users who have massive followers, influencers can mobilize and influence their followersÂ with very high feedback through the content they uploaded, therefore followers are often triggered to do OSD on their social media. The purpose of this study was to determine how significant the effect of the independent variable on the dependent variable, the motivation for online self-disclosing. The paradigm used is quantitative with correlational studies. The method of distributing the questionnaire was carried out by using a simple random sampling technique to 100 respondents who were followers of the @catwomanizer Instagram account. The results showed that the two variables simultaneously had a 0.620 degree of relationship with a strong correlation level.